Impact of children's ward design and layout to the hospitalized children : an architectural review - 191723 Nur Nawwar Ahmad Farouk (Skudai : Universiti Teknologi Malaysia, 2008)
Topical Study (Sarjana Muda Senibina) - Universiti Teknologi Malaysia, 2008